A new species of Syphacia (Seuratoxyuris) (Nematoda: Oxyuridae) from Sooretamys angouya Fischer, 1814 (Rodentia: Cricetidae) in Argentina - Robles, Maria del Rosario (2014)
Syphacia (Seuratoxyuris) hugoti n. sp. (Nematoda: Oxyuridae) is described from the cecum of Sooretamys angouya (Cricetidae: Sigmodontinae: Oryzomyini) captured in Formosa Province, Argentina. The diagnosis of the subgenus is emended, and the new species is separated from eight congeners by the distribution of submedian papillae and amphids, shape of the cephalic plate, presence of deirids, absence of cervical and lateral alae, length of the spicule, structure of the accessory hook of the gubernaculum and distance of excretory pore and vulva from the anterior extremity. The analysis suggests that S. (Se.) oryzomyos should be removed from Seuratoxyuris and redesignated as S. (Syphacia) oryzomyos n. comb. To date, of the species of Syphacia found in South and North American, 7 parasitize Oryzomyini rodents, of which two are distributed in Argentina. The present study constitutes the first record of the subgenus Seuratoxyuris from Argentina and the third record of a Syphacia species from rodents of the tribe Oryzomyini.